Extraction and Characterization of Chitosan and Preparation of Nanocomposites with Resorcinol Formaldehyde Resin - Bhandari, Ganesh; Pandit, Rajesh; Bhandari, Netra Lal (Journal of Nepal Chemical Society, 2018)
Available with full text.